ASSESSMENT OF THE SPATIAL DISTRIBUTION OF CHRONIC KIDNEY DISEASE IN HADEJIA EMIRATE, JIGAWA STATE - A.U, BAFFA; I. A., ABDULKARIM; N.A, YARO, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Chronic Kidney Diseases (CKD) is worldwide health crisis where globally 10% of the population is affected by the disease. CKD kills millions each year because they lack access to affordable treatment. This study examined the prevalence of CKD in Hadejia Emirate. Data was collected from General Hospital Hadejia which constituted records of 548 CKD cases from 2013-2018. GIS mapping and coordinates of wards in the Emirate were generated and imported into ArcGIS 10.3 software. Geospatial technique using Geographical Information System was employed to analyze the distribution of Chronic Kidney Disease in Hadejia Emirate. Moral’s I was used to determine Hotspot and Cluster of CKD. The distribution of CKD were shown using maps, and graphs were used to examine the Temporal pattern and Demographic characteristics. The result showed high prevalence in some wards which include Arki, Fandum, Fataika, Jabbo, Tonikutara, and Yankoli. The study also showed clusters in 2015 and of the study period with the highest z-score of 4.054909 observed in 2015. The monthly trend shows that mostly CKD cases occurred during the rainy season, particularly June/September and less significant in December/May. Wet season appears to strongly influence the occurrence of CKD. CKD in Hadejia Emirate has been traced to possible contamination of water sources due to the use of agrochemicals to improve agricultural production and pollutant from other upstream and within the wetlands area during the wet season. The study recommends reduction in the use of agrochemicals in farming activities and increased use of manure.